Variability, Heritability and Genetic Divergence in Pod and Seed Traits of Dalbergia Sissoo Roxb. in a Seedling Seed Orchard - Sofi, Altaf Hussain; Singh, Ombir (Indian Forester, 2013)
The variations present in seed and pod traits, genetic superiority and genetic divergence were evaluated for a Seedling Seed Orchard (SSO) of Dalbergia sissoo Roxb. at Bithmera, India consisting of 19 progenies from the state of Uttarakhand. The seeds and pods of various progenies in the orchard exhibited significant variability in size, weight and other characters. Significant positive correlations were observed between seed length and seed weight (P<0.01), seed width and seed weight (P<0.01), seed thickness and seed weight (P<0.05), seed weight and germination value (P<0.05), seed length and germination value (P<0.05). The genetic parameters for seed and pod traits also showeda wide range of variations. Heritability values were found to be over 50 for most of the seed and pod traits, however, only seed weight showed high heritability values coupled with maximum genetic gain. Ward's minimum variance dendrogram of progenies of D. sissoo showed three distinct clusters; cluster 1 with 6 better progenies, cluster 2 with 10 moderate and cluster 3 with 3 poor progenies. Mean cluster values showed sufficient variation among the clusters for seed weight, germination value and seed length. The possibility of controlled hybridization between better progeny (288) of cluster 1 to the disease resistant progeny (304) of cluster 3 (resistant against deadly Gandoderma lucidum root rot disease of D. sissoo) is also suggested for further breeding programmes of the species.